Conformational Flexibility in the Transmembrane Protein TSPO1. Issue 46 (23rd September 2015) - Jaremko, Łukasz; Jaremko, Mariusz; Giller, Karin; Becker, Stefan; Zweckstetter, Markus
Abstract: The translocator protein (TSPO) is an integral membrane protein that interacts with a wide variety of endogenous ligands, such as cholesterol and porphyrins, and is also the target for several small molecules with substantial in vivo efficacy. When complexed with the TSPO‐specific radioligand ( R )‐PK11195, TSPO folds into a rigid five‐helix bundle. However, little is known about the structure and dynamics of TSPO in the absence of high‐affinity ligands. By means of NMR spectroscopy, we show that TSPO exchanges between multiple conformations in the absence of ( R )‐PK11195. Extensive motions on time scales from pico‐ to microseconds occur all along the primary sequence of the protein, leading to a loss of stable tertiary interactions and local unfolding of the helical structure in the vicinity of the ligand‐binding site. The flexible nature of TSPO highlights the importance of conformational plasticity in integral membrane proteins. Abstract : Conformational flexibility : The structure and dynamics of the membrane translocator protein (TSPO), in the presence and absence of a strongly binding ligand, have been investigated by multidimensional NMR techniques. The results indicate extensive molecular motion in the absence of the ligand, leading to local unfolding of the helical structure, thus implying the importance of conformational flexibility in the interactions of membrane proteins.